Penerapan Sumber Daya Perusahaan (ERP) Dalam Meningkatkan Manajemen Rantai Pasok (SCM) Pada PT Pelat Timah Nusantara TBK - Zai, Immanuel; Aulia Qadri, Rizni; Fernando, Rio; Agustisan, Willien; Chandra Wijaya, Roger (GEMA EKONOMI, 2023)
The era of globalization causes business to develop rapidly. Business development leads to higher competition. The occurrence of globalization is accompanied by the development of technology. Currently, many companies are implementing ERP systems in their company's SCM. The implementation of ERP systems provides so many benefits for companies specialized in SCM. This research uses qualitative methods with a type of case study research. PT Latinusa Tbk is one of the companies engaged in processing and trading. PT Latinusa Tbk realizes the importance of implementing SCM in its business. Not only that, PT Latinusa Tbk also realizes the importance of implementing technology. Therefore, PT Latinusa Tbk implements an ERP system. The implementation of ERP system at PT Latinusa Tbk turns out to provide many benefits, especially to improve the performance of supply chain management. The improvement, effectiveness, and efficiency of the company's SCM are proof that the ERP system at PT Latinusa Tbk has been successfully implemented